Induction of a specific CD8+ T-cell response to cancer/testis antigens by demethylating pre-treatment against osteosarcoma - Li, Binghao; Zhu, Xiaobing; Sun, Lingling; Yuan, Li; Zhang, Jian; Li, Hengyuan; Ye, Zhaoming (Oncotarget, 2014)
Conventional non-surgical therapeutic regimens against osteosarcoma are subject to chemoresistance and tumor relapse, and immunotherapy may be promising for this tumor. However, it's hard to find satisfactory epitopes for immunotherapy against osteosarcoma. Cancer/testis antigens (CTAs), such as MAGE-A family and NY-ESO-1, the potential antigens that almost exclusively express in tumor cells and immune-privileged sites, have been found expressed in osteosarcoma also. Nevertheless, the expression of CTAs is downregulated in many tumors, constraining the application of immunotherapy. In this article, we demonstrate that the expression of MAGE-A family and NY-ESO-1 in osteosarcoma cells can be upregulated following treatment with demethylating agent 5-aza-2'-deoxycytidine and consequently induces a CTA specific CD8+ T-cell response against osteosarcoma in vitro and in vivo. The in vivo imaging was realized by using luciferase-transfected HOS cells and DiR labeled T-cells in severely combined immunodeficiency mouse models. Cytotoxic T cells specifically recognizing MAGE-A family and NY-ESO-1 clustered at the tumor site in mice pre-treated with DAC and resulted in tumor growth suppression, while it was not observed in mice without DAC pre-treatment. This study is important for more targeted therapeutic approaches and suggests that adoptive immunotherapy, combined with demethylating treatment, has the potential for non-surgical therapeutic strategy against osteosarcoma.